Framing Prahara Rumah Tangga Baim Wong-Paula Verhouven di Media Online: Perspektif Ruang Publik Habermas: Framing the Baim Wong-Paula Verhouven Household Dispute in Online Media: Habermas's Public Sphere Perspective - Tuty Ocktaviany; Kusumajanti Kusumajanti; Bekti Istiyanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study examines media coverage of actor Baim Wong's divorce lawsuit against Paula Verhoeven, which attracted widespread public attention after Baim publicly revealed Paula's alleged infidelity. Drawing on Robert N. Entman's framing theory and Jürgen Habermas's concept of the public sphere, this study examines how Indonesian online media framed the issue and its implications for public discourse. In Habermas's idealized conception of the public sphere, the media function as facilitators of rational and inclusive discussion; however, the research findings indicate that contemporary reporting practices are often driven by media agendas, audience appeal, and moral orientations that influence how events are interpreted. The analysis reveals differences between two major media outlets: Okezone.com tends to legitimize Baim Wong's actions by emphasizing narratives of moral justification and sympathy. At the same time, Detik.com adopts a more critical stance by questioning the ethics of disclosing personal conflicts in the public sphere and highlighting the diverse responses of netizens.Nevertheless, both media outlets prioritize sensationalism and emotional engagement over rational deliberation. These framing practices demonstrate a shift toward entertainment-based journalism that undermines the media's democratic function in fostering critical discussion. This study concludes that Indonesian media need to strengthen reporting ethics, accuracy, and respect for privacy to improve the quality of public discourse and maintain social harmony in the digital era.